Russia's Islamic threat - Hahn, Gordon M. (Yale University Press, 2007)
The book lifts the veil on the Muslim challenge to Russia's political stability, national security, and state integrity as well as the potentially grave threat to international and U.S. security. Hahn shows that many of the demographic, historical, socioeconomic, political, and religious factors sparking jihadi revolution in Muslim countries are extant in Russia and are driving revolutionary Islamist terrorism there. In a penetrating conclusion to the book, the author analyzes the policies that have fueled the rise of militant Islam and offers a series of important recommendations for policymakers.